Psychologization in and through the women's movement: a transnational history of the psychologization of consciousness-raising in the German-speaking countries and the United States - Ruck, Nora; Luckgei, Vera; Rothmüller, Barbara; Franke, Nina; Rack, Emelie (Journal of the history of the behavioral sciences, 2022)
This study explores the psychologization of the women's movement by examining the activist practice of consciousness-raising in a transnational perspective. We follow the lines along which P/psychological concepts that were appropriated and developed by North American feminist activists during the late 1960s and early 1970s traveled to the German-speaking countries and were translated, adopted, and transformed by feminist activists in Germany and Austria. We explore both the process of psychologization as the practice traveled from the United States to German-speaking countries and the various dimensions of psychologization: diffusion of Psy-expert discourse beyond the borders of the psy-disciplines, academization, individualization, and meta-psychologization. With the latter term, we aim to capture the relationship between (feminist) P/psychology and its critique.
Gesehen am 29.05.2023